Lintrik di Kalangan Akademisi Muslim - Karerina, Nina (Paradigma, 2021)
Abstract This research is motivated by the practice of shamanism which is still crowded with visitors in modern times, located in urban areas, namely Jambangan. These customers are dominated by Muslim academics. The purpose of this study is to identify the objective conditions of Muslim academics, identify the reasons for the use of electricity among Muslim academics, and analyze the motives for the cause and motivation of Muslim academics using lintrik. This research method uses qualitative research methods with the perspective of Alfred Schutz’s theory of phenomenology. The data obtained was carried out by means of observation, interviews and documentation. The results showed that Muslim academics had intersubjectivity, namely that they considered visiting a shaman as a form of effort / effort while still asking God with the aim of achieving the goals desired by the subject more quickly, the shaman was considered an intermediary between himself and God. Because the motive is, namely due to environmental factors, love problems, career problems, alternative treatments, and deadlocked. in order to motive is namely because it is to save / the integrity of the household, to obtain marital blessing, for relationship / household harmony, to remove pellets, for healing illness, for career interests. Keywords: Lintrik, Season Academic, Shaman